The Systematic Development and Pilot Randomized Evaluation of Counselling for Alcohol Problems, a Lay Counselor‐Delivered Psychological Treatment for Harmful Drinking in Primary Care in India: The PREMIUM Study. (19th February 2015) - Nadkarni, Abhijit; Velleman, Richard; Dabholkar, Hamid; Shinde, Sachin; Bhat, Bhargav; McCambridge, Jim; Murthy, Pratima; Wilson, Terry; Weobong, Benedict; Patel, Vikram
<x xml:space="preserve">Abstract</x> Background Despite harmful drinking causing a significant burden on global health, there is a large treatment gap, especially in low‐ and middle‐income countries. A major barrier to care is the lack of adequately skilled human resources to deliver contextually appropriate treatments. This paper describes the systematic process used to develop Counselling for Alcohol Problems (CAP), a brief psychological treatment (PT) for delivery by lay counselors in routine primary care settings to men with harmful drinking in India. Methods CAP was developed using a methodology involving 3 sequential steps: (i) identifying potential treatment strategies; (ii) developing a theoretical framework for the treatment; and (iii) evaluating the acceptability and feasibility of the treatment. Results CAP is a 3‐phase treatment delivered over 1 to 4 sessions based on a motivational interviewing (MI) stance and involves the following strategies: assessment and personalized feedback, family engagement, drink refusal skills, skills to address drinking urges, problem‐solving skills and handling difficult emotions, and relapse prevention and management. Data from a case series were used to inform several adaptations to enhance the acceptability of CAP to the recipients and feasibility of delivery by lay counselors of the treatment, for example expansion of the target group to include alcohol‐dependent patients and the extension of the delivery settings to include home‐based delivery. There was preliminary evidence of the effectiveness of CAP. Conclusions CAP is an acceptable brief PT for harmful drinking delivered by lay counselors in primary care whose effectiveness is currently being tested in a randomized controlled trial based in primary care in Goa, India.